Synthesis, Characterization, and Biological Evaluation of Some New Functionalized Terphenyl Derivatives. (13th December 2012) - Samshuddin, Seranthimata; Narayana, Badiadka; Sarojini, Balladka Kunhanna; Shetty, Divya N.; Suchetha Kumari, Nalilu
Abstract : New functionalized terphenyl derivatives incorporating various heterocyclic rings are prepared by using 4, 4′′-difluoro-5′-hydroxy-1, 1′:3′, 1′′-terphenyl-4′-carbohydrazide as a key intermediate derived from 4, 4′-difluoro chalcone, a versatile synthone. All the derivatives are characterized by 1 H NMR, IR, and mass spectral data. All the synthesized products are screened for their in vitro antimicrobial and antioxidant properties. The majority of the tested compounds exhibited significant antioxidant activity and some of them showed good antimicrobial activity.